Mg-rich synthetic gypsum application on soils in Malaysia to sustain agricultural production: a review - J., Shamshuddin; C.I., Fauziah; M.A., Mohd Firdaus; Ayanda, A. F. (Malaysian Society of Soil Science, 2021)
Applying Mg-rich synthetic gypsum (MRSG) on acid sulfate soils results in a concomitant alleviation of Al3+ and/or Fe2+ toxicity and is known to increase soil pH and improve rice growth. In the case of the oil palm, S is required in sufficient quantities to produce oil in its fruitlets. For all intents and purposes, MRSG can be used as Mg- and/or Ca-fertiliser for oil palm and rubber as well as for sustainable rice cultivation on acidic soils. Greater use of MRSG which is locally available would reduce imports of fertiliser and at the same time sustain agricultural productivity. This is translated into foreign exchange savings as well as increased income for farming communities. As it is available in large quantities in Malaysia, MRSG utilisation would sustain agriculture in the country at a reasonable cost. In conclusion, application of MRSG on acidic soils in Malaysia does not contribute to environmental degradation. Instead, the MRSG supplies Ca, Mg and S that are needed in high amounts by crops to sustain growth and/or production. Thus, we can turn the otherwise cheap by-product of a chemical plant into a useful fertiliser that contributes to our economic growth.